The solar shield concept: Current status and future possibilities. (August 2022) - Roy, Kenneth
Abstract: The concept of deploying a large solar shield, or sunshade, near the Sun-Earth L1 Lagrange equilibrium point was first proposed in 1989. The purpose of such a solar shade would be to reduce the quantity of solar radiation impinging on planet Earth, thus lowering the average global surface temperature and countering, to some extent, global warming. This form of solar radiation management seems to be one of the safest and most efficient methods proposed to date but also seems to be extremely expensive and perhaps too difficult to implement in a timely manner. The near-term arrival of cheap, re-useable launch vehicles may be able to address both of these concerns. Depending on the assumptions made, deploying a solar shield near the Sun-Earth L1 point might actually be feasible in the near term and would be able to slow, stop, or even reverse Earth's global warming, even in the face of increasing levels of greenhouse gases in Earth's atmosphere. Solar radiation management doesn't address other environmental issues, such as the acidification of the world's oceans, but it does address the more urgent issue of impending global warming and the resulting climate change, thus buying time for the World's economies to transition to more sustainable, carbon-free energy sources. The infrastructure necessary to construct and deploy a large solar shield will probably be space-based and could be useful for many other purposes after deployment of the solar shield. Highlights: Space Based solar shields can be used to address Earth's global warming. A solar shield is a collection of autonomous solar-sail craft acting together. Technologies needed for solar sail craft are well advanced. Reductions in launch costs from Earth make the solar shields idea viable. Infrastructure needed to deploy a solar shield can advance space exploration.